Integrating Heutagogy and Self-efficacy: Study on Bahtsul Masail-based Learning Design - Sirojuddin, Muhammad; Yaqin, Ainul (Journal of Pesantren and Diniyah Studies, 2024)
The learning design that aligns with students' characteristics and learning styles is a crucial focus for educators. This article is compelling as it highlights the Bahtsul Masa'il-based learning model, which offers a unique approach to enhancing self-efficacy through active engagement, independent learning, and critical thinking skills, particularly in the pesantren environment. This study aims to analyze the contribution of Bahtsul Masa'il in shaping students' self-efficacy through the heutagogy approach. Self-efficacy is formed through an individual's belief in their ability to achieve specific goals, including adaptability and critical thinking skills. Meanwhile, heutagogy is positioned as a self-directed learning strategy that places students at the center, encouraging active involvement in designing learning content and applying knowledge contextually. This research employs a descriptive qualitative method, collecting data through observations and interviews with Asatidz and Kitab Kuning learners at the Ulya and Wustho levels in Pondok Pesantren Assalafi Al Fithrah Surabaya. Data analysis techniques include triangulation. The findings reveal that Bahtsul Masa'il significantly enhances students' self-efficacy through active problem-solving, resilience development, confidence building, and peer learning support. The heutagogy approach complements this process by granting autonomy to students to identify problems, seek solutions, and apply knowledge independently while remaining guided by the Bahtsul Masa'il framework. These findings affirm that integrating both approaches is relevant to modern educational needs and effective in shaping independent, critical, and confident learners.